Nucleation and lateral growth kinetics of the NiSi phase at the epitaxial θ-Ni2Si/Si interface. (1st October 2020) - El Kousseifi, Mike; Hoummada, Khalid; Panciera, Federico; Lavoie, Christian; Mangelinck, Dominique
Abstract: The first stages of the growth of the NiSi phase at the expense of θ-Ni2 Si have been studied mainly by in-situ XRD measurements and atom probe tomography (APT) analysis. In-situ XRD isothermal annealing at different temperatures were performed on several samples in order to monitor the phase formation sequence, the time at which NiSi phase begin to form and its growth kinetics. These results show that while the phase formation sequence is the same, the time for the beginning of formation of NiSi varies from one sample to the other under the same isothermal temperature and experimental conditions. Comparing these findings with nucleation and growth models, the growth of the NiSi phase at the expense of θ-Ni2 Si is controlled by nucleation compared to diffusion in the case of δ-Ni2 Si as the first phase. The kinetics for the nucleation and lateral growth of the NiSi phase were deduced and the implications for the formation of this phase and for contacts are discussed. Graphical abstract: Image, graphical abstract